SOSIALISASI PENGGUNAAN BLOG SEBAGAI STRATEGI PEMASARAN BUAH PINANG DI DESA SIDODADI - Khairunnisa Khairunnisa; Siti Sundari; Ade Irwan (Jurnal Abdimas Bina Bangsa, 2021)
Sidodadi Village is a village in the Batang Kuis sub-district, Deli Serdang Regency, North Sumatra Province, Indonesia. One of the businesses in Sidodadi village is the Home Industry for marketing betel nuts which was initiated in 2012 by Mr. Mahadi and his wife, Mrs. Yayuk Wulan Dari. From the survey results, it turns out that partners have several problems, including the lack of knowledge and skills possessed by partners regarding product marketing techniques. The marketing method used by partners is still conventional, namely offering products by conveying information about their products and trying to persuade consumers to want to buy. During the covid pandemic, like today, partners feel the sales of betel nuts are decreasing. Therefore, partners need several steps to be able to maintain the business that the partners have built so far. The step or solution offered to partners is to use internet services, namely by providing socialization on the use of blogs to increase the marketing of areca nuts owned by partners